Pyrite as a catalyst for the emergence of multiphase primitive cells - Ding, Niannian; Ren, Tianhao; Liang, Dehai; Dong, Hailiang (Frontiers in Microbiology, 2026)
Coacervate-based protocells are minimal systems that mimic certain properties of natural cells and are used to investigate the emergence of life from nonliving chemical systems. However, constructing protocells with hierarchical structures and life-like functions remains a challenge. In this work, we develop a novel coacervate-based protocell (droplet) composed of single-stranded oligonucleotides (ss-oligo), quaternized dextran (Q-dextran), and 3,3′,5,5′-tetramethylbenzidine (TMB). In the presence of natural pyrite, the droplet encapsulates the pyrite, enhancing its peroxidase-like catalytic activity. This activity catalyzes oxidation of TMB to its oxidized form (TMBox), inducing a transition from single-phase to multiphase droplets. The resulting multiphase droplet consists of an internal TMBox/ss-oligo phase and a surrounding Q-dextran/ss-oligo phase, facilitating the sequestration and partitioning of ss-oligo into discrete regions. Notably, these droplets exhibit stability in their internal sub-compartments during fusion, showing their potential as dynamic and functional models in synthetic biology and biotechnology applications. Our study highlights that the catalytic activity of minerals may serve as a potential strategy for constructing hierarchically structured protocells that resemble the morphology and functions of living cells. This finding represents a significant step towards improving our mechanistic understanding of the transition from non-living matter to living systems under prebiotic conditions.